Prevalence and prognostic impact of unrecognized myocardial infarction detected by cardiac magnetic resonance in Thai patients with obesity - Punyanuch Chayanopparat; Piyachai Siriphiphatcharoen; Issarayus Laohabut; Thanawat Ruengchaisiwawaith; Yodying Kaolawanich (PLoS ONE, 2026)
Background Unrecognized myocardial infarction (UMI) is associated with adverse outcomes and may occur in patients with obesity, who are at increased cardiovascular risk. Although cardiac magnetic resonance (CMR) enables accurate detection of UMI, prognostic data in patients with obesity remain limited, particularly in Asian populations. This study evaluated the prevalence and prognostic impact of CMR-detected UMI in Thai patients with obesity. Methods This cohort study included 1,053 patients with BMI ≥ 25 kg/m 2 , without a prior diagnosis of myocardial infarction (MI) or coronary revascularization (mean age, 67 ± 11 years; 71.3% grade 1 and 28.7% grade 2 obesity), who underwent CMR at an academic hospital in Thailand between 2014 and 2016. The most common indication was suspected coronary artery disease (78.3%). UMI was identified using late gadolinium enhancement imaging. Patients were followed for major adverse cardiovascular events (MACE), defined as a composite of cardiovascular death, nonfatal MI, or hospitalization for heart failure. Results UMI was identified in 105 patients (9.9%). During a median follow-up of 9.2 (5.2–10.2) years, patients with UMI had a significantly higher rate of MACE compared with those without UMI (2.58 vs. 0.89 per 100 patient-years; HR, 2.86; 95% CI, 1.68–4.88; p < 0.001). In multivariable analysis, age, diabetes, cigarette smoking, history of heart failure, LVEF, and UMI were independently associated with MACE. The presence of UMI provided incremental prognostic value beyond traditional risk factors (Δχ 2 = 22.43; p < 0.001). Across all subgroups defined by age, sex, obesity grade, diabetes status, symptoms, LVEF, and myocardial ischemia, UMI was consistently associated with higher risks of MACE, with no significant interactions observed (all p for interaction>0.05). Conclusions In Thai patients with obesity undergoing CMR, the prevalence of UMI was 9.9% and was independently associated with MACE, providing incremental prognostic value. These findings suggest that CMR-detected UMI may play a role in risk stratification in this population.